Identification of platelet function defects by multi-parameter assessment of thrombus formation - de Witt, Susanne M.; Swieringa, Frauke; Cavill, Rachel; Lamers, Moniek M. E.; van Kruchten, Roger; Mastenbroek, Tom; Baaten, Constance; Coort, Susan; Pugh, Nicholas; Schulz, Ansgar; Scharrer, Inge; Jurk, Kerstin; et al. (Nature communications, 2014)
Assays measuring platelet aggregation (thrombus formation) at arterial shear rate mostly use collagen as only platelet-adhesive surface. Here we report a multi-surface and multi-parameter flow assay to characterize thrombus formation in whole blood from healthy subjects and patients with platelet function deficiencies. A systematic comparison is made of 52 adhesive surfaces with components activating the main platelet-adhesive receptors, and of eight output parameters reflecting distinct stages of thrombus formation. Three types of thrombus formation can be identified with a predicted hierarchy of the following receptors: glycoprotein (GP)VI, C-type lectin-like receptor-2 (CLEC-2)>GPIb>α 6 β 1 , α IIb β 3 >α 2 β 1 >CD36, α 5 β 1 , α v β 3 . Application with patient blood reveals distinct abnormalities in thrombus formation in patients with severe combined immune deficiency, Glanzmann’s thrombasthenia, Hermansky–Pudlak syndrome, May–Hegglin anomaly or grey platelet syndrome. We suggest this test may be useful for the diagnosis of patients with suspected bleeding disorders or a pro-thrombotic tendency. Platelets from patients with bleeding disorders often display altered adherence to surface proteins. In this study, de Witt et al. design a flow chamber for the systematic interrogation of platelets attaching to 52 adhesive surfaces, which may be helpful for the diagnosis of platelet disorders.